The Good Corporate Governance: Case Study in Indonesia and Philippines - Werner R. Murhadi; Anastasia Handoyo; Endang Ernawati (Universitas Muhammadiyah Yogyakarta, 2024)
Good corporate governance is critical in reducing conflict between agencies in the workplace. Corporate governance is crucial in developing nations with lax law enforcement. The impact of governance on corporate performance is investigated in this article. This study uses quantitative data from manufacturing companies registered on the Indonesian and Philippine stock exchanges. This study relied on 655 observations from Indonesia and 220 from the Philippines. Corporate governance is measured using independent commissioners, the number of board members, shareholder ownership, and the use of Big Four auditors. This study discovered that independent commissioners, the board size, and block-holders ownership significantly affected the return on assets. Tobin's Q analysis revealed that only Board Size had a significant effect. Unlike Indonesia, the results of this study in the Philippines showed that independent commissioners and block holder ownership significantly impacted the return on assets. On the other hand, this study using Tobin’s Q showed that all independent variables, such as independent commissioners, the board size, block-holders ownership, and big four accounting firms, had a significant effect. The practical implication of the study's findings is that management monitoring by independent commissioners and all commissioners is beneficial in avoiding managers' acts that harm the organization. On the one hand, the number of commissioners sends an excellent signal to the market. Block holder ownership and the usage of big four accounting firms can also strengthen monitoring, improving corporate performance. Companies should have a high proportion of independent commissioners, a modest board size, and use big four accounting firms. Companies can increase their performance and investor trust by applying the above governance components.